2004
DOI: 10.1128/jcm.42.4.1505-1510.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and Coalescent Phylogenetic Analysis of Pneumocystis jiroveci from South Africa

Abstract: Sequence analysis of Pneumocystis jiroveci internal transcribed spacer (ITS) regions has become an important epidemiological tool. The objectives of the present study were to investigate sequence variations in the ITS1-5.8S ribosomal DNA (rDNA)-ITS2 regions; determine the P. jiroveci genotypes present in Cape Town, South Africa; and resolve the lineage evolution of the types by use of the coalescent theory. ITS regions were amplified from samples collected from 19 patients. PCR products were cloned, and four t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
3
28
0
1
Order By: Relevance
“…In addition to these observations, ITS typing data have recently been presented as indicative of the occurrence of genetic recombination in P. jirovecii populations (17,21). Although the results reported here cannot be used to draw specific conclusions about clonal or recombining modes of reproduction in P. jirovecii, they do suggest that meiotic recombination in the rDNA of this fungus is not a frequent event.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition to these observations, ITS typing data have recently been presented as indicative of the occurrence of genetic recombination in P. jirovecii populations (17,21). Although the results reported here cannot be used to draw specific conclusions about clonal or recombining modes of reproduction in P. jirovecii, they do suggest that meiotic recombination in the rDNA of this fungus is not a frequent event.…”
Section: Discussionmentioning
confidence: 77%
“…To date, more than 30 ITS1 genotypes and 40 ITS2 genotypes with more than 90 haplotypes (combinations of ITS1 and ITS2 types) have been described worldwide, based on two different but similar typing systems (8,26). Some ITS haplotypes are globally more common, and coinfections with multiple types of P. jirovecii often occur (4,8,11,15,17,25,26). Although these typing systems have been useful, questions have been raised about the extensive polymorphism and stability of the ITS locus and its use for the genotyping of P. jirovecii.…”
mentioning
confidence: 99%
“…P. jirovecii ITS genotypes were aligned with previously published and unpublished genotypes (GenBank accession no. AF013806 to AF013834, AF374238 to AF374265, AF498265, AF135711 to AF135712, AY328043 to AY328066, AY550105 to AY550109, and AF013835 to AF013840) (13,23,24,26,27,29,31). The mt LSU rRNA genotypes were characterized based on the polymorphic sites at codons 85 and 248: genotypes 1 (85:C/248:C), 2 (85:A/248:C), 3 (85:T/248:C), and 4 (85:C/248:T) (12).…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing of ITS regions from five clones per specimen demonstrated that the P. jirovecii isolates harboring the DHFR C200T transitions had ITS genotypes Eg and Eu. Interestingly, ITS type Eu, which to date has only been found in South Africa (12), was associated with the DHFR mutation Ala67Val. Furthermore, the DHFR mutation Arg59Gly and the intron transition mutation C278T have not previously been described.…”
mentioning
confidence: 99%
“…For strain typing, amplification of the internal transcribed spacer (ITS) region of the rRNA gene was performed (7), and PCR products were subcloned prior to sequencing (12). The ITS sequences obtained were compared to those of published ITS regions, and type nomenclature was assigned in accordance with Lee et al as described by Robberts et al (12).…”
mentioning
confidence: 99%